THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS AND THE ADMINISTRATIVE EFFICIENCY OF SARKIES 'AISYIYAH KUDUS HOSPITAL - Ria Febrianti; Muhammad Purnomo; Fitriana Kartikasari; Zunia Khairunnisa (PT. Radja Intercontinental Publishing, 2026)
The digital transformation of healthcare services has encouraged hospitals to implement Electronic Medical Records (EMR) as an effort to improve administrative efficiency and service quality. This study aims to analyze the relationship between the implementation of Electronic Medical Records (EMR) and administrative efficiency at Sarkies 'Aisyiyah Hospital in Kudus. The study used a quantitative method with a correlational analytical design and a cross-sectional approach. The study population consisted of 155 administrative staff and medical record officers, all of whom were sampled using a total sampling technique. Data were collected using a Likert scale questionnaire that has been declared valid and reliable, then analyzed using univariate analysis and the Spearman Rank correlation test with the help of SPSS. The results showed that the implementation of Electronic Medical Records was in the high category (89.7%) and administrative efficiency was in the efficient category (98.1%). Bivariate analysis showed a significant relationship between the implementation of Electronic Medical Records and hospital administrative efficiency (p < 0.001; r = 0.514). This study concluded that increasing the implementation of Electronic Medical Records is associated with increased hospital administrative efficiency. Optimizing system integration, strengthening technological infrastructure, and improving human resource competencies are needed to support the success of the digital transformation of healthcare services.